COLORFUL LIFE HEALTHY LIFE - Bharti, Vandana (International Journal of Research -GRANTHAALAYAH, 2014)
The information provided in this article is to obtain a further understanding of the beneficial health effects of various food pigments naturally occurring in plant products. The bright colors of many vegetables contribute much to their appeal. The colors result from the various pigments contained in their tissues. Most of the pigments occur in plastids –specialized bodies lying in the protoplasm of the cell. Sometimes the water – soluble pigments are dissolved in the vacuoles and not generally distributed throughout the cell. Thesepigments display various colors and are made up of different phytochemicals commonly found in the food matrix such as orange (β-carotene), yellowish-green (lutein), green (chlorophyll), and blue-purple (anthocyanin). Lycopene is the red colored pigment abundantly found in red colored fruits and vegetables such as tomato, papaya, pink grapefruit, pink guava and watermelon.